Determinan Pengungkapan Islamic Social Reporting (ISR) pada Perbankan Syariah di Indonesia (Determinants of Islamic Social Reporting (ISR) Disclosure at Islamic Commercial Banks in Indonesia) - Arianugrahini, Ikkama; Firmansyah, Egi Arvian (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to analyze the factors that affect the disclosure of Islamic Social Reporting (ISR) in the annual report of Islamic Commercial Banks (BUS) in Indonesia for the 2014-2018 period. The method used in selecting the sample in this study was sampling using 55 samples which were determined based on the sample criteria in this study. Hypothesis testing in this study uses multiple linear regression analysis. ISR is evaluated based on content analysis by analyzing the annual reports of 11 Islamic Commercial Banks (BUS) in the 2014-2018 period. The results of this study indicate that, simultaneously, all independent variables have a positive effect on ISR. Firm size has a significant effect on ISR, while company age, profitability, leverage, and cost efficiency have no significant effect on ISR. It does not affect company age, profitability, leverage, and cost efficiency because these variables are not directly related to the ISR disclosure.